2006
DOI: 10.1152/ajpcell.00074.2006
|View full text |Cite
|
Sign up to set email alerts
|

ATP and PIP2 dependence of the magnesium-inhibited, TRPM7-like cation channel in cardiac myocytes

Abstract: The Mg 2ϩ -inhibited cation (MIC) current (I MIC) in cardiac myocytes biophysically resembles currents of heterologously expressed transient receptor potential (TRP) channels, particularly TRPM6 and TRPM7, known to be important in Mg 2ϩ homeostasis. To understand the regulation of MIC channels in cardiac cells, we used the whole cell voltage-clamp technique to investigate the role of intracellular ATP in pig, rat, and guinea pig isolated ventricular myocytes. I MIC, studied in the presence or absence of extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 47 publications
3
58
1
Order By: Relevance
“…5). Other studies also have shown that PIP 2 Nanodiscs bind Ca 2þ and Mg 2þ differently (61), but they conflict in that some report that PIP 2 lipids bind Ca 2þ more strongly and others report that PIP 2 lipids bind Mg 2þ more strongly (61,62). For example, Ca 2þ has been observed to induce stronger aggregation behavior than Mg 2þ (57,61); however, we did not observe Ca 2þ -induced aggregation with PIP 2 Nanodiscs.…”
Section: Popacontrasting
confidence: 74%
“…5). Other studies also have shown that PIP 2 Nanodiscs bind Ca 2þ and Mg 2þ differently (61), but they conflict in that some report that PIP 2 lipids bind Ca 2þ more strongly and others report that PIP 2 lipids bind Mg 2þ more strongly (61,62). For example, Ca 2þ has been observed to induce stronger aggregation behavior than Mg 2þ (57,61); however, we did not observe Ca 2þ -induced aggregation with PIP 2 Nanodiscs.…”
Section: Popacontrasting
confidence: 74%
“…Kir, KCNQ1, and P/Q-type Ca 2ϩ channels) regulated by PIP 2 (41). Although PIP 2 and related phosphoinositides exert positive effects on the activity of many TRP channels, such as TRPV5 (32), TRPM4 (35,44), TRPM5 (45), TRPM7 (46,47), TRPM8 (33,34), and TRPC6 (7,48), it is inhibitory to few others, such as dTRPL (3) and TRPV1 (42, 49). Ironically, the inhibitory effect of PIP 2 on TRPV1 has been challenged by more recent studies showing the activating effect of PIP 2 on TRPV1 in inside-out patches (50,51).…”
Section: Discussionmentioning
confidence: 99%
“…One involved examining the effects of phenylarsine oxide on Cdc42-mediated transformation, given the reports that it inhibits PIP 2 production in cells by blocking the actions of phosphatidylinositol 4-phosphate kinase (27,28). Supplemental Fig.…”
Section: Disrupting the Interaction Between Cdc42 And Pip 2 Selectivementioning
confidence: 99%